Effective Reward System on Hospital Staff Performance: Challenges and Solutions (A Qualitative Study in Hospitals Affilliated to Tehran Universitu of Medical Sciences) - Azadeh Sayarifard; farid Abolhasani; Laleh Ghadirian; Maryam Nazari; Fatemeh Rajabi; Leila Haghjou; Leila Mounesan (Tehran University of Medical Sciences, 2017)
Background: Reward system program is an investment tools in order to improve quality of services. Accordingly, this study was conducted aimed to identify the challenges of the reward system and the solutions for improving that based on the views of stakeholders in Tehran University of Medical Sciences hospitals. Materials and Methods: This directional content analysis qualitative study was performed in Tehran University of Medical Sciences during 2014and 2015 using content analysis method. Targeted sampling was done and in-depth semi structured and face to face interviews were performed with a wide variety of experts and professionals including managers, faculties and hospital staffs. After word by word transcripting and extracting codes (meaningful phrases), these codes was reviewed again in order to achieve subcategories. Based on subcategories, information was classified to assossiated  categories. For validity and reliability checking, stakeholders and faculties member check and peer debriefing were used.Results: Eventually, a total of 29 interviews were held. The comments were classified within 6 main categories, 19 subcategories and 1100 codes. The main categories included existing arrangements in hospitals in order to improve staff motivation; reward system challenges; derived opportunities from rewarding experiences; rewarding systematic actions; types of appropriate rewards and making infrastructure for better rewarding system implementation. Conclusion: Regarding multiple aspects of a reward system which could have an effective role in increasing staff motivation or a contradictory effect when it is inefficient, implementation of an effective reward system in hospitals by designing an appropriate model based on identified key factors in this study, is recommended.